BRCA1 founder mutations do not contribute to increased risk of gastric cancer in the Polish population. Issue 1 (December 2016) - Ławniczak, Małgorzata; Jakubowska, Anna; Białek, Andrzej; Lubiński, Jan; Jaworska–Bieniek, Katarzyna; Kaczmarek, Katarzyna; Starzyńska, Teresa
Abstract Background Gastric cancer (GC) is part of the spectrum of diseases linked toBRCA1 andBRCA2 mutations that increase the risk of breast and ovarian cancer. Data suggesting an increased risk of developing GC amongBRCA1 andBRCA2 mutation carriers are based almost exclusively on indirect studies. The objective was to assess in a direct study whether there is a relationship between GC and selected recurrentBRCA1 andBRCA2 mutations in the Polish population. Methods Three hundred seventeen GC patients (193 males and 124 females; mean age 59.5 ± 12.8 y) diagnosed at the Department of Gastroenterology at the Pomeranian Medical University were included in this retrospective study. All patients were genotyped for 3BRCA1 Polish founder mutations (5382insC, C61G and 4153delA) as well as for 9 known recurrent mutations inBRCA1 andBRCA2 genes. Genotyping was performed using allele-specific oligonucleotide polymerase chain reaction (ASA-PCR) for 4153delA and 5382insC, restriction fragment length polymorphism (PCR-RFLP) for C61G and TaqMan real-time PCR for 185delAG, 3819del5, 3875del4, 5370C > T, 886delGT, 4075delGT, 5467insT, 6174delT and 8138del5. Results Among tested mutations one founderBRCA1 mutation 5382insC was detected in two of 317 (0.63 %) GC cases. A comparison of frequency of detectedBRCA1 founder mutations in GC patients to previously described 4570 Polish controls (0.63 % vs. 0.48 %) failed to indicate an increased risk of GC in the mutation carriers (OR = 1.3; 95 % CI 0.3-5.6, p  = 0.71). A comparison of frequency of GC male cases and male controls (1.0 % vs. 0.43 %, OR = 1.5; 95 % CI 0.3-6.4, p = 0.61 ) allowed to formulate the same conclusion that there is no increased risk for GC for males. None of the 9 recurrentBRCA1 andBRCA2 mutations has been detected in tested GC patients. Conclusion The current study indicates that founderBRCA1 mutations reported in Polish breast/ovarian cancer patients do not contribute to increased GC risk. The nine tested recurrentBRCA1 andBRCA 2 mutations were not detected in GC patients which may suggests that they are rare in GC patients in the Polish population. Further analyses, including sequencing of entire sequences ofBRCA1 andBRCA2 genes, are necessary to ultimately determine the role of these two genes in GC in Poland.